Etude comparative entre la glycémie capillaire et la glycémie veineuse à l’hopital mixte El Akid Lotfi de Laghouat - BAROUD KHEIREDDINE ALLAL (université ammar telidji laghouat, 2025)
Abstract Blood glucose monitoring is an essential component of diabetes management. Inaccurate blood glucose measurements can have serious consequences on patient health. This study evaluated locally manufactured test strips. Our study is defined as a pilot study that evaluates two locally manufactured capillary SAGs according to the FDA: 2014 guideline and ISO 15197: 2013 standards under university conditions. To this end, we determined blood glucose levels in 102 patients using two SMBG systems, compared to an automated system using the reference method (Automated). Indeed, our study shows, after a statistical comparison, a significant difference for glucometer 1 with a t = 4.18 and a compliance of 44%, which is well below the standard requirements. Résumé 120 Glucose meter 2, on the other hand, has a t = 0.0263 and a compliance of 73.08%, an improvement, but still below the required thresholds. Therefore, the accuracy assessment shows that both systems tested do not meet the requirements of ISO 15197:2013. Although the systems do not comply with strict analytical standards, this inaccuracy is associated with no clinical risk or minimal clinical risk. The study evaluating blood glucose self-monitoring strips is therefore feasible under the following conditions: Algerian. Keywords: diabetes - capillary blood glucose self-monitoring system - analytical performance - ISO 15197
CD-ROM